Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Simple and large-scale preparation of HPAMAM/PVA sponge with robust mechanical properties for hexavalent chromium adsorption - Ji Gao; Li Cai; Lingfeng Zhang; Cunwei Fan; Hao Zhang; Jie Sun; Kai Guo (Journal of Environmental Chemical Engineering, 2026)

HMGB1 blockade attenuates cardiac injury induced by radiotherapy combined with PD-1 inhibitor while maintaining the anti-tumor efficacy - Yao Liu; Lingfeng Liu; Bibo Wu; Jing Zhang; Chaofen Zhao; Bing Lu; Yinxiang Hu; Weiwei Ouyang; Zhenneng Guo; Rong Hu; Shengfa Su (Apoptosis, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Multifunctional polyvinyl alcohol composites via melt blending with a bio-based P-N synergistic flame retardant: Achieving simultaneous enhancement in fire safety, UV shielding, and mechanical properties - Junsheng Guo; Wenzong Xu; Tao Yan; Jiayan Zhang; Xiaoyu Guo; Lingfeng Wang; Julan Liu (Chemical Engineering Journal, 2026)

A refined incremental homogenization approach for heterogeneous nonlinear geomaterials without isotropization - Yongdong Li; Yuanming Lai; Zhaomin Lv; Xinwen Wang; Yian Zhou; Zipeng Qin; Lingfeng Guo; Lunyang Zhao (Computers and Geotechnics, 2025)

Ultra-stable and pH-universal photoelectrochemical photodetector achieved by CdSeTe/ZnS core-shell quantum dots - Jian Zhang; Yule Zhang; Songrui We; Han Zhang; Lingfeng Gao; Hao Wang; Chunxian Guo (Chemical Engineering Journal, 2025)

An incoherent feed-forward loop coordinates nitrate uptake and tillering in wheat - Weiya Xu; Yongming Chen; Yanxiao Niu; Bin Liu; Dejie Du; Xining Ning; Tong Huan; Yilan Zhou; Wensheng Ke; Lingfeng Miao; Weilong Guo; Mingming Xin; et al. (Molecular Plant, 2025)

Urban vegetation productivity under climate change and increasing urbanization: Insights from both urban-rural comparison and trend analysis for global cities - Jiuyi Chen; Bo Qiu; Weidong Guo; Xin Miao; Yipeng Cao; Zhihan Zhao; Siwen Zhao; Lingfeng Li; Yueyang Ni; Shihan Tang; Limei Yang (Urban Forestry & Urban Greening, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

A multiscale generative adversarial network approach for generating porous media with structural morphology - Yafei Xu; Lingfeng Guo; Danqing Song; Yi Shan; Xiaoli Liu (Stochastic Environmental Research and Risk Assessment, 2025)

Correction: Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Near-complete assembly and comprehensive annotation of the wheat Chinese Spring genome - Zijian Wang; Lingfeng Miao; Kaiwen Tan; Weilong Guo; Beibei Xin; Rudi Appels; Jizeng Jia; Jinsheng Lai; Fei Lu; Zhongfu Ni; Xiangdong Fu; Qixin Sun; et al. (Molecular Plant, 2025)

Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

A unimodal soil-water characteristic curve model for gap-graded soil based on bimodal grain-size distribution and fractal theory - Yuefeng Wu; Junsheng Chen; Weidong Pan; Lingfeng Guo; Yi Shan (Transportation Geotechnics, 2025)

Ion separation with graphene oxide nanofluidic membranes: A review - Dekang Pang; Lingfeng Liu; Xiaojing Zhang; Changsheng Guo; Jianbo Jia; Changyu Liu; Mengchen Zhang (Desalination, 2025)

Saline seepage circulation experiment study on low plastic limit clays combined with microscale tests and the fractal theory - Lingfeng Guo; Yingguang Fang; Yafei Xu; Renguo Gu; Shufeng Bao; Yi Shan (Bulletin of Engineering Geology and the Environment, 2024)

Janus graphene oxide membrane with rational allocation of functional regions as unidirectional ion valve system - Jundong Yan; Lingfeng Liu; Zhichen Liang; Chongfeng Huang; Wenbiao Zheng; Changsheng Guo; Minchao Liu; Chao Peng; Jianbo Jia; Mengchen Zhang (Desalination, 2024)

Bioorthogonal surface-edited exosomes for targeted multimodal imaging and synergic chemophototherapy of oral cancer - Yuxiao Wu; Xiaofeng Shan; Yuanjie Zhang; Wen Shi; Xingxing Zhu; Mengfan Yu; Shang Xie; Lingfeng Guo; Zhiqian Chen; Chuanling Zhang; Demin Zhou; Zhigang Cai (Chemical Engineering Journal, 2024)

FSP1-mediated ferroptosis in cancer: from mechanisms to therapeutic applications - Ran Gao; Jinge Wang; Jingjing Huang; Tong Wang; Lingfeng Guo; Wenlu Liu; Jialu Guan; Desen Liang; Qinghui Meng; Huayang Pan (Apoptosis, 2024)

Research and application of a tunnel active–passive cooperative control mechanism - Qi Wang; Lingfeng Sun; Bei Jiang; Zhongxin Xin; Yueru Guo (Tunnelling and Underground Space Technology, 2024)

Impact of dielectric barrier discharge cold plasma on anthocyanin metabolism in blueberries: A targeted metabonomic and transcriptomic analysis - Lingfeng Xu; Zhenbo Gao; Ling Li; Jian Guo (Postharvest Biology and Technology, 2024)

A new multiscale Cosserat model for size effect simulation in granular media - Lingfeng Guo; Xiaolong Li; Lu Ren; Yuanming Lai; Junsheng Chen; Lunyang Zhao (Computers and Geotechnics, 2024)

Rain gardens enhance the taxonomic richness but not the abundance of soil invertebrates in urban ecosystems - Jingjing Wang; Lihao Guo; Saige Xu; Yan Zhu; Lingfeng Mao (Ecological Engineering, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Growth patterns and optimum habitat of Larimichthys crocea throughout ontogenesis based on a bioenergetics model - Bin Xie; Shin-ichi Ito; Lingfeng Huang; Haiqing Yu; Chenying Guo; Ziqin Wang (Regional Studies in Marine Science, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

Enhancing effect of cobalt phthalocyanine dispersion on electrocatalytic reduction of CO2 towards methanol - Tianxiang Guo; Xilai Wang; Xiaodong Xing; Zhixiang Fu; Changxin Ma; Alemayehu Hailu Bedane; Lingfeng Kong (Environmental Science and Pollution Research, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Performance of potentiometric oxygen sensors with LSCF electrode in lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Lingfeng Yang; Muran Qi; Xiaobo Li; Yifeng Wang; Zhenhua Sheng; Xu Tu; Gaoxiang Xu; Boqing Li; Hao Wu; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Halide-chalcogenide hetero-structure for efficient and stable perovskite solar cells - Riming Nie; Zeliang Wei; Aarti Mehta; Lingfeng Chao; Jiaxing Gao; Weicun Chu; Zhongping Li; Han Miao; Yonghua Chen; Wanlin Guo (Chemical Engineering Journal, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Water mass-driven multiple ecological effects determine the biodiversity and community assembly of microbial flagellates in subtropic-tropic marginal seas of China - Xin Guo; Qiang Liu; Xiaoqing Lin; Xinyi Zheng; Cheng Huang; Mengwen Pang; Lingfeng Huang (Estuarine, Coastal and Shelf Science, 2023)

Niche overlap and divergence times support niche conservatism in eastern Asia–eastern North America disjunct plants - Xue Yin; Scott Jarvie; Wen‐Yong Guo; Tao Deng; Lingfeng Mao; Minhua Zhang; Chengjin Chu; Hong Qian; Jens‐Christian Svenning; Fangliang He (Global Ecology and Biogeography, 2021)
Aim The plant species sharing ancestors now disjunctly distributed in eastern Asia (EAS) and eastern North America (ENA) have long been a biogeographic puzzle. Species within the EAS–ENA disjunct genera are presumed to exhibit niche conservatism, the tendency of closely related species to be more ecologically similar, reflecting lineages’ common evolutionary history. However, the hypothesis has not been well examined at the species level. Location EAS and ENA. Time period Current. Major taxa studied Species within the EAS–ENA disjunct genera. Methods We compiled data on climate, species occurrence, growth form, and phylogeny to examine niche conservatism. We first built a phylogenetic tree to select intercontinental congeneric pairwise species and obtained their divergence times. We then quantified the observed niche overlaps with Schoener’s D , which has a 0–1 range, based on species occurrence and climate of species’ native ranges. To obtain projected distributions, each species’ niche was projected to the non‐native region using ensemble ecological niche models. Projected‐related niche overlaps were then calculated using projected distributions and the corresponding climatic conditions. Results Average observed niche overlaps of congeneric pairwise species were relatively small: .124, .211 and .109 for all, herbaceous and woody species, respectively. Both observed and projected‐related niche overlaps had significant negative relationships with divergence times of intercontinental congeneric pairwise species, with niche overlap for herbaceous species being higher than that for woody plants when controlling for divergence times. Main conclusions We conclude that the significant negative relationships between niche overlap and divergence times of congeneric pairwise species confirm niche conservatism among species of EAS–ENA disjunct plants and that the extent of niche conservatism is slightly different for herbaceous and woody plants. These findings suggest the potential role of allopatric speciation in EAS, and could help to understand the evolutionary history and the Asian‐bias diversity pattern of the EAS–ENA disjunct plants.

Mitogenomic phylogeny of Trochoidea (Gastropoda: Vetigastropoda): New insights from increased complete genomes - Erfei Guo; Yi Yang; Lingfeng Kong; Hong Yu; Shikai Liu; Zhanjiang Liu; Qi Li (Zoologica Scripta, 2021)
Increased mitochondrial (mt) genomes can provide more sets of genome‐level characteristics for resolving deeper phylogeny. Limited information with respect to the Trochoidea mitochondrial genome organization is available; besides, monophyly and internal relationships of the superfamily still remain a matter of discussion. To resolve the monophyly and internal phylogenetic controversies of Trochoidea and expand our understanding for mt genomic characteristic evolution among Trochoidea, the phylogenetic trees were reconstructed using 13 newly sequenced complete mt genomes and 35 genomes from GenBank, and both the maximum likelihood and Bayesian inference analyses were highly supported. Vetigastropoda phylogenetic analyses recovered the monophyly of Trochoidea. Trochoidea phylogenetic analyses and genetic distances supported the non‐monophyly of Tegulidae and Tegula , indicating that the taxonomic status of several genera ( Rochia , Tectus and Cittarium ) should be revised and Tegula , Omphalius and Chlorostoma should be placed as a same genus. The close affinity between Tectus virgatus and Rochia was also revealed. Three‐nucleotide insertion in nad1 , nine‐nucleotide insertion and six‐nucleotide deletion in nad5 are detected in Tegulidae, Tectus and Rochia , respectively. Gene orders within Trochoidea are stable, with gene rearrangements exclusive to tRNA genes observed. Homoplasious convergences because of trnT rearrangement display translocation in Turbinidae and reversion in Trochidae and Calliostomatida. For trnE and trnG , we identify 11 arrangement types, suggesting that the gene rearrangement history needs to be further evaluated. Our study emphasizes the importance of mt genomes in resolving phylogenetic relationships within Trochoidea. In addition, the mt genomic characters would contribute new insights into the classification of Trochoidea.

Mechanism test on inhomogeneity of dredged fill during vacuum preloading consolidation - Yingguang Fang; Lingfeng Guo; Junwen Huang (Marine Georesources & Geotechnology, 2019)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Linkage disequilibrium in wild and cultured populations of Pacific oyster (Crassostrea gigas) - Xiang Guo; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

QTL mapping for glycogen content and shell pigmentation in the Pacific oyster Crassostrea gigas using microsatellites and SNPs - Xiaoxiao Zhong; Qi Li; Xiang Guo; Hong Yu; Lingfeng Kong (Aquaculture International, 2014)

Molecular cloning and differential expression in tissues of a tyrosinase gene in the Pacific oyster Crassostrea gigas - Xue Yu; Hong Yu; Lingfeng Kong; Fengguang Guo; Guan Zhu; Qi Li (Molecular Biology Reports, 2014)

Microbial community of aerobic granules for ammonium and sulphide removal in a sequencing batch reactor - Caili Su; Lingfeng Zhu; Chuan Zhang; Xianghui Qi; Yiping Guo; Ruqin Gao (Biotechnology Letters, 2012)